Pemanfaatan Aplikasi Quizizz dalam Pembelajaran Peserta Didik Kinestetik di Kelas VII E SMP Negeri 2 Sewon Tahun Ajaran 2022/2023 - Wildan Ghufron; Asep Purwo Yudi Utomo; Martina Puspita Rakhmi; Sab’ah Ashfiya Adiratna Salim Putri; Iwan Hardi Saputro; Durratus Sa'diyah; Meilia Meilia (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Technology can be used to find solutions to learning problems. The learning problems encountered were students who were active at SMPN 2 Sewon on descriptive text material. Teachers need to know the characteristics of students to solve problems. One of the uses of technology to overcome this problem is by looking for the characteristics of students and the results of using the quizizz application in learning descriptive text in class VII E SMPN 2 Sewon. The aims are (a) to find out the characteristics of students and (b) to find out the learning outcomes with the Quizizz application. This study uses a quantitative descriptive method as well as observation and interview techniques, and notes to find data. The results of the data were processed and analyzed according to qualitative descriptive research. The results of the study found that the characteristics of students have a kinesthetic learning style. In addition, it was concluded that the use of the Quizizz application could have a major effect on learning descriptive text in class VII E of SMPN 2 Sewon. The average value reaches 95 when using the quizizz application with a kinesthetic learning style approach.